At your command A basic english workbook / Patricia licklider - Licklider, Patricia (United states América: little brown and company, 1980)
Finding tre verb, finding thebverb changing the time of the sentence finding the auxiliary verbs lookimg for verbs in contractions using verbs to find fragments; finding the subject, finding the subject, subjects with prepositional phrases, subjects and shifer, inverted sentences, compound subjects, verbs, and sentences, compound subjects compound verbs; complex sentences versus fragments, complex sentences versus fragments, finding dependent clause fragments,using subordinating words, review of sentence typen; run-0ns,however, moreover, thereforre,leaming to use the semicolon correctly; subject-verb agreement, the-ending on nouns and verbs, some agreement rules; problems with verbs, simple past tenses, missing -ed, the perfect tenses, passive voice -ed words adjectives; problems with pronouns, crear pronoun reference, choosing the right pronoun form;tangled sentences, misplaced modifeiers, dangling modifiers, vocabulary using definitions and synonyms, understanding connotations and levels of usage, using words figuratively; spelling, some spelling, rules, homonyms and other confusing word twins, the spelling.
Contents, glossary appendix points to remember
Col. Educ
Keywords: 1. ENGLISH BASIC 2. EDUCATIÓN